Wpływ stopnia rozdrobnienia kolb kukurydzy na wydajność procesu fermentacji = Influence of kolb corn size reduction on the yield of digestion process - Jędrczak, Andrzej; Królik, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article have been presented the results of the impact of fragmentation colb of corn on productivity of methane during fermentation process, carried out under conditions of meso- and thermophilic. It was shown that the biogas production during mesophilic fermentation almost linearly increased with increasing fineness of the waste, while for the thermophilic digestion of waste, fragmentation was not significantly affected the quantity and composition of biogas production and the degree of conversion of waste.
Keywords: fermentacja mezofilowa; fermentacja termofilowa; biogaz; kolby kukurydzy; mesophilic fermentation; termophilic fermentation; biogas; corn of colb